Applying the Rasch Model to Investigate Habit of Mind Pre-service Teacher - Meyta Dwi Kurniasih; YL Sukestiyarno; Rochmad Rochmad; Amin Suyitno (Universitas Negeri Semarang, 2022)
The habit of mind mathematics is an intelligent behavior that affects individual success because by having this behavior students can quickly and precisely find complex solutions to mathematical problems. This study aims to identify the habit of mind of mathematics teacher candidates based on their indicators. This quantitative study applies the Rasch model with as many as 245 research subjects as prospective teacher students in the 2021/2022 academic year. Rasch analysis is used because it assumes parameter invariance, meaning that the statement item parameters do not depend on the teacher candidate's ability parameters and vice versa. The Habit of mind instrument was used in the form of a questionnaire with 7 (seven) indicators totaling 54 statements. Before the questionnaire is used, face and content validity are carried out by experts. The results of Rasch's analysis show that the habit of mind mathematics possessed by prospective teachers in each class is different. Upper-semester students have a better habit of mind than early-semester students.